2013
DOI: 10.1017/s1742170513000057
|View full text |Cite
|
Sign up to set email alerts
|

Exploring risk management strategies for organic farmers: A Greek case study

Abstract: This study attempts to enrich the debate on the different forms of risk management strategies that are utilized by organic farmers and to assess the internal dynamics within the organic farming community by examining the attitudes and practices of these farmers. In particular, using a factor analysis, this study determines the attitudes of Greek farmers toward risk management strategies and focuses on the differences in risk attitudes between existing organic farmers and non-organic farmers. Second, using a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…Firstly, it is expected that the more information on biosecurity threats and management strategies are available, the better farmers' cope with threats and minimize future risks. Previous research has confirmed the positive relationship between the receipt of information and farmers' decision-making in management strategies, in the context of organic agriculture (Tzouramani et al, 2013) and climate change (Dang et al, 2014). This study aims to empirically test the relationship between biosecurity information and biosecurity risk coping appraisal: H1: Information on biosecurity risk management strategies is positively related to biosecurity risk coping strategies (higher response efficacy, higher self-efficacy and lower response costs).…”
Section: Hypothesesmentioning
confidence: 95%
See 1 more Smart Citation
“…Firstly, it is expected that the more information on biosecurity threats and management strategies are available, the better farmers' cope with threats and minimize future risks. Previous research has confirmed the positive relationship between the receipt of information and farmers' decision-making in management strategies, in the context of organic agriculture (Tzouramani et al, 2013) and climate change (Dang et al, 2014). This study aims to empirically test the relationship between biosecurity information and biosecurity risk coping appraisal: H1: Information on biosecurity risk management strategies is positively related to biosecurity risk coping strategies (higher response efficacy, higher self-efficacy and lower response costs).…”
Section: Hypothesesmentioning
confidence: 95%
“…Factor analysis was used to determine which biosecurity risk management strategies tended to cluster across respondents. This technique has been used widely in agriculture to categorize the clusters of risk management strategies that farmers employed (Tudor et al, 2014, Tzouramani et al, 2013).…”
Section: Framework Hypotheses Case Studies and Data Analysismentioning
confidence: 99%
“…Tzouramani et al (2014), for example, showed that Greek farmers enter off-farm activities to buffer their risk. Work satisfaction may also play a role: Carrying out rather specialized and monotonous tasks is less satisfying than being engaged in a broad range of activities, in agriculture and beyond (Besser and Mann 2015).…”
Section: Part-time Farmingmentioning
confidence: 99%
“…This leads to a rather narrow focus on identifying general risk factors, such as pests and disease and price volatility (Aimin, 2010), along with risk management strategies such as consultancy and disease prevention (Flaten et al, 2005b). In relation to organic farming, ways of managing risk include crop rotations, learning networks, cooperatives (Hanson, Dismukes, Chambers, Greene, & Kremen, 2004) as well as liquidity (keeping cash in hand), controlling the costs of production, using insurance (Flaten et al, 2005a), producing at the lowest cost and seeking professional consultancy (Tzouramani, Alexopoulos, Kostianis & Kazakopoulos, 2013). A study by Trujillo-Barrera et al, (2016) found that risk perception has a negative effect on adoption of sustainable practices, particularly when one's livelihood is at stake.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Risk perceptions can range from seeing no risk at all to seeing high risk (Trujillo-Barrera, Pennings & Hofek, 2016). It is argued that since alternative farming systems appear to be highly exposed to risk, it is important to examine the types of risk management strategies adopted by growers (Tzouramani, Alexopoulos, Kostianis & Kazakopoulos, 2013).…”
Section: Introductionmentioning
confidence: 99%